GAMBARAN TINGKAT PENGETAHUAN DAN DUKUNGAN KELUARGA PADA LANSIA DENGAN HIPERTENSI DI WILAYAH PONDOK PUCUNG RT 005/001 TANGERANG SELATAN TAHUN 2023 - Nuraini Sukmawati; Purwanti, Heni; Suheti (Jurnal Kesehatan STIKes IMC Bintaro, 2024)
Introduction : Hypertension is one of the diseases with the highest prevalence inthe world, one in four people in the world has high blood pressure, with a total ofmore than 1 billion people affected. As we age, the incidence of high bloodpressure also increases, one-third of patients live in developed countries and twothirds in developing countries, high blood pressure is estimated to cause 7.1million deaths, accounting for about 1.3% of all deaths worldwide. ResearchMethod The type of research used is quantitative, this research method isanalytical using a cross sectional approach. Descriptive Design Research wherethis researcher in collecting data is carried out at one point in time or at one pointin time and each object is only observed once. (Swarjana, 2015): Results of thestudy: age of 40 elderly Most of them were aged 60-69 years, namely as many as28 respondents (70%). With Elderly Knowledge about Hypertension Of 40Elderly Respondents, most of them were Less than 21 respondents (52.5%),Conclusion: Based on the category The level of knowledge with elderlyhypertension obtained less than 21 respondents (52.5%). As well as familysupport with elderly hypertension, good results were obtained with 27 respondents(67.5%).